Kebutuhan Lahan Pertanian Minimum untuk Kesejahteraan Petani di Pulau Sumatera - Baiq Rindang Aprildahani; Chrisna Trie Hadi Permana; Surya Tri Esthi Wira Hutama (Journal of Science and Applicative Technology, 2021)
The stream of sustainable city-region pinpoints the need to build an enhanced life support system. While it is expected to provide adequate foods for the current and future generation, the agriculture sector is, nevertheless, facing a challenge to sustain amidst the current massive urban sprawl. The study presents a case study of Western Indonesia, which is considered as one of the vast growing regions. The growth of urban centres creates a centrifugal force, resulting in a leapfrog development towards the outskirts, which usually causes the loss of prime agricultural lands. Existing planning documents were also unable to control the sprawling phenomenon, which impact at the current setback of farmers’ well-being. Previous studies show that the ability of peri-urban agriculture to accommodate self-provision of food and to ensure adequate income for farmers appear as the most prominent motivation which encourage farmers to stay engaged in farming sectors (Adrianto et al., 2013). Overall, this study uses qualitative analysis to investigate opportunities to preserve agriculture land by find out the requirement of agriculture land for farmer’s well being. This research comparing the minimum wage of each province in Sumatera and the income of farmers from agricultural production, so it is known that farmers on the island of Sumatra must have an average land area of 0.85 hectares to achieve welfare.